Scientific literacy refinement at Islamic junior high schools using socio-science spirituality learning model - Mimien Henie Irawati Al-Muhdhar; Resty Rahmatika; Muhamad Amin; Hadi Suwono (JPBI (Jurnal Pendidikan Biologi Indonesia), 2022)
Learners need to possess scientific literacy in order to be able to analyze and explain scientific concepts and solve daily life problems. The current study aimed to analyze the potential of the Socio-Science Spirituality learning model to improve the scientific literacy of students at the junior high school level. The sample of this research contained eight-grade students from an Islamic based school in Surabaya. A quasi-experimental design was used in this study involving the Socio-Science Spirituality class as the experimental group and the conventional class as the control group. Data were collected using multiple choice tests where the questions were developed based on 37 scientific literacy indicators. The data were analyzed using ANCOVA. The results showed that the application of the learning model influenced students’ scientific literacy, where the Socio-Science Spirituality group increased their scientific literacy 28.37% higher than the conventional group. In short, the Socio-Science Spirituality learning model has a higher potential to increase students’ scientific literacy, so that it can be used as a new reference to empower students’ scientific literacy.